The alcoholdehydrogenase activity and bioelements content in liver of rats under alcohol intoxication development - Степанець, І. О.; Кудрявцева, А. Г.; Харченко, О. І.; Войтенко, В. В.; Остапченко, Л. І. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2013)
The reduction of alcohol dehydrogenase activity by 49% on the 28th day in liver under alcohol intoxication development has been shown. It has been found that metal cations content in liver homogenate 11 days after introduction of ethanol is changed slightly. More pronounced changes of bioelements have been observed on the 28th day: Cu2+ reduced by 17%, Fe2 + and Ca2+ increased by 33% and 20% respectively. Zn2+ and Mg2+ content changed slightly.